Metodologia de sala de aula invertida no ensino-aprendizagem de biologia na 3ª série do ensino médio - Fazza, Luiz Francisco Alves (Universidade do Vale do Rio dos Sinos, 2021)
The Active Methodologies, mainly flipped classroom, applied to the teaching of Biology, comes as a possibility of qualifying the teaching and learning process. Based on the perspective described above, this study aims to understand how the flipped Classroom methodology can be used to contribute to the teaching-learning of Biology classes in the high school senior students (12th year). Besides that, the specific objectives are focused on the following actions (i) understand the theoretical concepts about the Flipped Classroom in the Biology class; (ii) get to know the previous teachers profiles about the proposed theme, in the perspective of the students and the parents; (iii) design and produce the online material to be available for the students during the flipped classroom; (iv) make use of the flipped classroom for presenting the Biology concept of “Speciation and reproductive isolation”; (v) analyze the understanding of the teaching and learning process based on the students and parents perspectives; (vi) comprehend students routine related to the online resources made available; (vii) provide subsidies, as possibilities of intervention, aiming to qualify the understanding of the contribution degree that these new pedagogical practices, mainly the flipped classroom, can offer. In order to address and answer all the research questions, the present work was carried out through a mixed methods case study and both morning high school senior students (12th year)and their parents answered structured questionnaires before and after the use of the Flipped Classroom, during the Covid-19 pandemic. The results indicate collective satisfaction concerning Flipped Classroom as the interviewees emphasized that this methodology allows interaction among students as well as collaborates with their autonomy towards study management, memorization of contents and an increase in their interest in learning. According to the responses received, the use of asynchronous video classes, before the face-to-face class, have contributed greatly to the active learning. Besides that, the activities done during the synchronous classes, when students could interact and have teachers help and support, promoted a better individual performance in other activities as well.
Keywords: Sala de aula invertida; Estudo de biologia; Ensino médio; Metodologias ativas; Tecnologias digitais; Flipped classroom; Biology study; High school; Activies methodologies; Digital technologies; ACCNPQ::Ciências Humanas::Educação